THE EFFECTS OF WORKLOAD AND SHIFT WORK ON NURSES' WORK STRESS AT MAYJEND HM RYACUDU REGIONAL GENERAL HOSPITAL - Silvia Iin Murni; Hendri Dunan; Haninun (International Journal of Multidisciplinary Reseach, 2026)
Nurses face continuous service demands, complex clinical responsibilities, and rotating work schedules that may increase occupational stress. This study examined the effects of workload and shift work on nurses' work stress at Mayjend HM Ryacudu Regional General Hospital, North Lampung Regency. A quantitative design using descriptive and verification approaches was applied. The entire population of 105 nurses was included through saturated sampling. Data were collected through observation, questionnaires, and documentation and were analyzed using validity and reliability tests, a normality test, multiple linear regression, partial t-tests, a simultaneous F-test, and the coefficient of determination. Workload had a positive and significant effect on work stress (t = 3.294; p = 0.001), while shift work also had a positive and significant effect (t = 19.277; p < 0.001). Simultaneously, workload and shift work significantly affected work stress (F = 1,264.762; p < 0.001). The model explained 96.1% of the variance in nurses' work stress, while 3.9% was attributable to factors outside the model. These findings highlight the need for proportional workload distribution, balanced shift scheduling, and adequate recovery time to support nurses' well-being and service quality.